Entre a face e a alma habitam as diferenças: Case Study Houses (EUA) | Casas Paulistas e Cariocas (BR) | Casas nos Jardins do Pedregal (MX), 1945 – 1960 - Vidal, Wylnna Carlos Lima (2019)
The thesis discusses the repercussions, in the Latin American context, of single-family houses built in the United States from 1945 until the late 1960's. In order to do so it takes as reference the projects realized under the Californian Case Study House Program (CSH, 1945 – 1966) and analyzes them in parallel to houses built in Brazil, particularly in São Paulo and Rio de Janeiro, and houses built in Mexico, particularly in the Jardins do Pedregal in Mexico City. Assuming that the diversity of contexts - sociocultural, economic and technical - in the United States, Brazil and Mexico had repercussions on the making of their respective domestic spaces, the thesis seeks to identify, on the one hand, which principles of design of domestic space disseminated by the CSH program may have been adopted by Brazilian and Mexican architectural contexts and, on the other hand, verify the nature of the adaptations made in the two countries through the transfer process and the need to accommodate the US references to local realities. From the comparison between similarities and singularities identified among the samples of houses from São Paulo and Rio de Janeiro, as well as from houses built in the Jardins do Pedregal, compared to the Case Study Houses, it becomes clear the contradictory mixture of the yearnings for progress, expressed more clearly in the external appearance of Brazilian and Mexican houses (in the ‘face’), and attachments to traditional modes and values, expressed spatially within the houses (in the 'soul'), attributes that describe the attraction of the American way of life and the limits of its acceptance in the Brazilian and Mexican contexts.